Reduction of Osx expression in the osseointegration process of dental implants with human adipose-derived mesenchymal stem cell intervention: an experimental study - Rachman, Arif; Arfiyanti, Arfiyanti; Reza Rahmana, Muhammad Dimas (Universitas Padjadjaran, 2025)
ABSTRACT Introduction: Peri-implantitis, an inflammatory response affecting the hard and soft tissues surrounding a dental implant, ultimately leads to a loss of osseointegration. Human adipose-derived mesenchymal stem cells (hADMSCs), sourced from adipose tissue, have high biocompatibility and regenerative capacity, with advantages such as self-renewal, plasticity, and multilineage differentiation. Alveolar bone repair using hADMSC has been demonstrated in periodontitis animal models through the STRO-1, RUNX-2, Osx (Osterix), and COL-I pathways. This study utilized hADMSC intervention to analyze Osx’s impact on the osseointegration process of Y-TZP. Methods: This experimental study employed Wistar rats, divided into six treatment groups (three for week 1 and three for week 8) and one negative control group. The study design was a randomized post-test only control group. After Y-TZP scaffold implantation for one and eight weeks, histological analysis identified Osx expression on the mandibular bone surface of Rattus norvegicus albinus Wistar strain rats. Immunohistochemistry (IHC) results for Osx expression were compared using a One-Way ANOVA test for data analysis. Results: hADMSC cells reached optimal proliferation and maturity by passage 4, suitable for Y-TZP scaffold seeding. Characterization confirmed positive CD105, CD73, CD90, and negative CD45, CD34, CD14, CD19, HLA-DR expression. ANOVA (p<0.05) and post-hoc HSD showed significant Osterix differences, except between treatment groups P2, P3, and P4. Conclusion: Intervention with hADMSCs in Y-TZP dental implants can potentially overcome dental implant failure, as evidenced by a decrease in Osterix expression during osseointegration. This decreased Osterix expression facilitates osteoblast formation and promotes the homing of hADMSCs.KEYWORDS: Osx expression, hADMSC, osteointegration, dental, implants